2016
DOI: 10.4172/2151-6219.1000237
|View full text |Cite
|
Sign up to set email alerts
|

What are the Impact of Foreign Aid to the Economic Growth? Time Series Analysis with New Evidence from Tanzania

Abstract: Despite the fact that, Tanzania is receiving large inflows of foreign aid since 1970s to support its economic activities. Yet, very few literatures investigated the impact of foreign aid to economic growth of Tanzania. After revealing that, despite the large inflows of foreign aid in Tanzania, the economic growth rate is apparently low, poverty level and budget deficits is still persisting over the economy. Thus our study intends to further investigate the impact of foreign aid to economic growth by using Dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…This result is inconsistent with the expected positive signs of foreign aid theories (see aforementioned). But the negative result is consistent with several empirical studies such as Griffin and Enos (1970), Weisskopf (1972), Papanek (1972) from old literature and Mallik (2008), Gitaru (2015), Mitra and Hossain (2013) , Albiman (2016) and Ferreria and Simoes (2013) from the recent literature. This negative growth effect could be due to several reasons: first as observed by Burnside and Dollar (2004), foreign aid can negatively affect growth in the absence of good policies and second, as observed by Mallik (2008), foreign aid is more likely to have a negative impact on growth if it is directed to more humanitarian aid rather than aid directed to production sectors.…”
Section: Empirical Modelsupporting
confidence: 89%
See 2 more Smart Citations
“…This result is inconsistent with the expected positive signs of foreign aid theories (see aforementioned). But the negative result is consistent with several empirical studies such as Griffin and Enos (1970), Weisskopf (1972), Papanek (1972) from old literature and Mallik (2008), Gitaru (2015), Mitra and Hossain (2013) , Albiman (2016) and Ferreria and Simoes (2013) from the recent literature. This negative growth effect could be due to several reasons: first as observed by Burnside and Dollar (2004), foreign aid can negatively affect growth in the absence of good policies and second, as observed by Mallik (2008), foreign aid is more likely to have a negative impact on growth if it is directed to more humanitarian aid rather than aid directed to production sectors.…”
Section: Empirical Modelsupporting
confidence: 89%
“…Mitra and Hossain (2013) found a similar result for the Philippines over the period of 1970–2010, and Gitaru's (2015) paper on Kenya over the period 1970–1995 also found a negative impact on growth. Finally, Albiman (2016) found that aid had a negative impact on growth in Tanzania over the period of 1976–2014 (see Table III).…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Empirical estimations showed aid-growth relationship to "U-inversion," meaning a strong diminishing return relationship. More, [25], [26] revealed a negative impact of foreign aid on economic growth. The influence of foreign aid and domestic savings on economic growth in WAMZ countries was studied [27] which leads to negative impact of foreign aid on economic growth.…”
Section: Research Elaborationsmentioning
confidence: 99%
“…Despite these large sums received in the form of aids and assistance from advanced countries, Nigeria still wallows in poverty and perpetually experiences economic downturn. In 2018, Nigeria records the highest number (about 91.8 million) of extremely poor people in the world, it records negative growth of real GDP per capital for 2015, 2016and 2017(WDI, 2018 and unemployment rate stood at 21.3% (NBS, 2018). In a bid to ameliorate the demeaning economic situation, the government of Nigeria has embarked on various journeys to advance countries seeking one form of aid or the other.…”
Section: Introductionmentioning
confidence: 99%